Integration of AI and Machine Learning with Snowflake: How Snowflake is Enabling Advanced Analytics and AI-Driven Insights in Cloud Environments - Nookala, Guruprasad (International Journal of Artificial Intelligence, Data Science, and Machine Learning, 2025)
Snowflake’s cloud-native data platform is helping artificial intelligence (AI) and machine learning (ML) to be combined to change how companies evaluate and use data in modern cloud environments. This paper investigates how Snowflake’s unique architecture—characterized by its decoupled storage and processing layers, scalable data sharing mechanism, and natural support for varied data workloads offers an amazing foundation for AI-driven analytics. The aim is to make obvious how Snowflake improves the acceptance and application of advanced analytics—that is, data intake, transformation, real-time model deployment, and insight production. This paper investigates fresh approaches, including Snowpark for machine learning processes, integration with well-known AI/ML tools, and facilitation of unstructured data and external operations, thereby exhibiting how Snowflake provides seamless, scalable, and safe AI testing and deployment. The paper also highlights pragmatic Snowflake use where companies democratize data access, simplify machine learning lifecycle management, and enable group development among engineers and data scientists. Snowflake’s technical ability is simply one aspect of its transformational potential; another is its ability to let businesses of all kinds quickly and successfully turn raw data into predictive insights more rapidly than ever before. Snowflake becomes a powerful tool for artificial intelligence at scale in the cloud as enterprises rapidly adopt intelligent decision-making, therefore tying current, AI-enhanced business intelligence with traditional data warehousing